Punishing corporate crime : legal penalties for criminal and regulatory violations - O'Reilly, James T., 1947- (Oxford University Press, 2009)
Punishing Corporate Crime: Legal Penalties for Criminal and Regulatory Violations provides a practical discussion of criminal punishment trends directed at the corporate entity. Corporate punishment, for the most part, has traditionally occurred either in the form of a fine or, in the extreme, a heavy sanction that terminates the business. This timely book analyzes the historical and statutory bases of corporate punishment and reviews the latest remedies now employed by the government, including receivership and monitoring, disgorgement of profits, restitution, integrity agreements, and disbar.